SISTEM INFORMASI PROMOSI DAN MUTASI PEGAWAI PADA PT. PLN (PERSERO) PEMBANGKITAN SEKTOR KOTA JAMBI EX PLTD KASANG: Information System;Promotion and Employee Mutation;Web. - Surya, Junaidi; -, Mulia (JURNAL AKADEMIKA, 2020)
PT. PLN (Persero) Jambi City Sector Power Plant is a state-owned company that deals with all aspects of electricity. So far in the management of promotional data and employee mutations are still using the manual way and by recording the activities on the record books and promotion of employee records, resulting in waste of time and data delays resulting in inefficient. Information presented such as making a report often has a delay due to the long time for processing so it can not be presented at any time. It causes the functions associated with the operational activities of PT. PLN (Persero) Pembangkitan Sector of Kota Jambi ex PLTD Kasang can not be implemented optimally. In this thesis report is made information system of promotion and employee mutation used to assist or facilitate manager of PT. PLN in managing employee data in the form of data input branch, job data, employee data, promotion data, employee mutation data and will produce output that is report of promotion data and employee mutation report. Software development using Web programming language using SQL database. From this research resulted a design of information system of promotion and mutation of employees that can facilitate data management of PT. PLN in data processing employees and making reports.